FAMILY NURSING CARE WITH DIABETES MELLITUS PROBLEMS READINESS TO INCREASE FAMILY COPING: A CASE STUDY IN LAMONGAN - Wijayanti, Endah Sri; Iswatun, Iswatun; Kurniawati, Rizka (Journal of Vocational Nursing, 2021)
Introduction : Family is an important aspect in nursing. Family members need care, supervision, and attention if they suffer from  health problems such as Diabetes Mellitus. Families must have effective and competent coping to overcome health problems of family members. Global DM prevalence in 2019 an estimated 9,3% (463 million people). DM patients in Lamongan regency are 1,4% with a total of 4,138 cases per year and are ranked 4th in Java Province. According to an integrated disease surveillance report based on Puskesmas in Lamongan. The percentade of DM in the last 2 years was 12 cases, based on data from Banjarejo village, Sukodadi. District, Lamongan Regency in 2020 as many as 6 patients from 450 patients. Method : Method this research uses a descriptive method in the form of a case study to axplore the problem of family nursing care in the case of Diabetes Mellitus with nursing problems of increasing family coping readiness in Banjarejo village, Sukodadi district, Lamongan regency. The approach used is a nursing care approach that includes assessment, nursing diagnosis, planning,implementation, and evaluation. Result : Patients usually then do things that are not allowed in the treatment process, such as not maintaining a pattern of nutrition, activity, and wound care. Discussion: The role of the family is needed because it has a duty in health so that they understand the health problems of family members with each other so that they can have a positive impact.